Monitoring Performance of Electric Utilities : Indicators and Benchmarking in Sub-Saharan Africa - Tallapragada V.S.N., Prasad; Shkaratan, Maria; Izaguirre, Ada Karina; Helleranta, Jaakko; Rahman, Saifur; Bergman, Sten (World Bank, Washington, DC, 2013)
Performance of electric utilities is essential for the reform of the electricity sector in the Sub-Saharan Africa (SSA) countries. The World Bank is leading a number of initiatives to improve electric utility performance in SSA. The Africa Energy unit of the World Bank recently introduced the Electric Utility Capacity Assistance Program (EUCAP) for Africa. Among other activities, the EUCAP aims to collate relevant utility performance data within the context of the Bank operations, with the dual objective of assessing the impact of reforms and motivating utility management to achieve better outcomes. In order to reach this objective, performance benchmarking approach was developed. In this approach, benchmarking starts with the selection of the Key Performance Indices (KPIs) reflecting major elements of utility day-to-day operations, including technical, operational and financial. Then a framework to compare performance of the sector in various countries and among utilities using these indices is applied.